Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1080/09638190802137083
|View full text |Cite
|
Sign up to set email alerts
|

Exchange rates and US direct investment into Latin America

Abstract: This paper analyzes the impact of exchange rate levels and exchange rate uncertainty on US foreign direct investment into Latin America. By decomposing exchange rate uncertainty into temporary (short-run) and permanent (long-run) components, we further explore whether the nature of uncertainty matters. Our empirical findings support the view that exchange rate uncertainty has a negative impact on US investment flows into Latin America. Moreover, it is the persistency in uncertainty rather than transitory uncer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Greenaway et al (2012) on the other hand discovered that multinational enterprises whose origin was outside the European Union (EU) were the least affected by exchange rate volatility whilst the multinational enterprises from the EU region were found to be more susceptible to exchange rates changes. Moreover, Ruiz and Pozo (2008) found out that exchange rate volatility negatively impacted on FDI from the US into Latin American countries (Argentina, Brazil, Chile, Colombia, Mexico, Peru and Venezuela) during the period between 1994 and 2005. The same study by Ruiz and Pozo (2008) revealed that persistency in exchange rate volatility is the one that resulted negative FDI inflow from the US to the Latin American countries.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Greenaway et al (2012) on the other hand discovered that multinational enterprises whose origin was outside the European Union (EU) were the least affected by exchange rate volatility whilst the multinational enterprises from the EU region were found to be more susceptible to exchange rates changes. Moreover, Ruiz and Pozo (2008) found out that exchange rate volatility negatively impacted on FDI from the US into Latin American countries (Argentina, Brazil, Chile, Colombia, Mexico, Peru and Venezuela) during the period between 1994 and 2005. The same study by Ruiz and Pozo (2008) revealed that persistency in exchange rate volatility is the one that resulted negative FDI inflow from the US to the Latin American countries.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Moreover, Ruiz and Pozo (2008) found out that exchange rate volatility negatively impacted on FDI from the US into Latin American countries (Argentina, Brazil, Chile, Colombia, Mexico, Peru and Venezuela) during the period between 1994 and 2005. The same study by Ruiz and Pozo (2008) revealed that persistency in exchange rate volatility is the one that resulted negative FDI inflow from the US to the Latin American countries.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“… Because of space issues we do not elaborate on the control variable results, but they may differ from previous work (see Montero 2008; Ruiz and Pozo 2008; Agostini and Raquel Jalile 2009; Tuman 2009) because of various differences, including lack of a proper judicial/rule of law indicator and/or difference in the years and countries used in the studies. …”
mentioning
confidence: 99%